Effect Of Self-Efficacy And Organizational Culture On Subjective Career Success In High School Teachers - Khairul Adabi; Desi Yustari Muchtar (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
This research aim to know the level of subjective career success on teachers, because teachers is the most important pillar in the educational system. Based on the previous study, there are many factors that influence subjective career success, such as self-efficacy and organizational culture. Sel-efficacy is regarded as one of the most important factors in subjective career success (Abele & Spurk, 2012). Besides that, organizational culture have positively influence concerning to subjective career success (Erdogan, Kraimer & Liden, 2004). Samples amount in this research is teachers in senior high school in south Tangerang. Sampling technique in this study was nonprobability sampling with 203 respondents. This study used quantitative approach with linear regression as analysis method.Finding from this study explains that self-efficacy organizational culture such respect for people influence significantly on subjective career success on teachers. It is accordance with the finding of previous studies conducted by Abele and Spurk (2012) and Erdogan, Kraimer, and Liden (2004) that self-efficacy and organizational culture influence on subkective career success. DOI: 10.15408/tazkiya.v22i1.8159